(untitled) (Applied Biological Research, 2022)
In present study the statistical optimization of process parameters for cost effective production of polygalacturonase (PGase) by Bacillus subtilis was examined by using Plackett-Burman design (PBD) and central composite design (CCD). Of the 9 factors, temperature, CaCO3 and KH2PO4 were found significant by PBD and were further optimized by CCD. After optimization, maximal PGase activity (272.87 Um L-1) was achieved at 40°C, 3.5 mM concentration of KH2PO4 and 6.5 mM concentration of CaCO3. The results showed 2.95-fold increase in PGase activity of B. subtilis under optimized conditions. Thus, it may be concluded that optimized medium is cost-effective and suitable for maximum production and may be used for large-scale PGase production by B. subtilis KP10B. The crude enzyme extracts of B. subtilis can be used in industry for fruit juice clarification, waste water treatment and coffee fermentation.